CHEMICAL COMPONENTS OF THE ESSENTIAL OILS FROM THREE SPECIES OF MALAYSIAN PLUMERIA L. AND THEIR EFFECTS ON THE GROWTH OF SELECTED MICROORGANISMS - Shaida Fariza Sulaiman,; Salmy Suhaida Yaacob,; Tan Mei Lan,; Tengku Sifzizul Tengku Muhammad, (Tropical Life Sciences Research, 2008)
The chemical components of the essential oils obtained from the flowers of three Malaysian species of Plumeria, namely P. rubra L. (red flower variety), P. acutifolia Poir. (yellow flower variety) and P. obtusa L. (white flower variety) were analyzed by GC/MS and 27 components were identified. Seven components were separated and identified from P. rubra, 14 components from P. obtusa and 19 components from P. acutifolia. The major component that is found in all three species is 2-hydroxybenzoic acid phenylmethyl ester. Those three species also shared two alkane hydrocarbons, that is nanodecane and heneicosane. The antimicrobial properties of the essential oils (at 2 ?l per disk) were determined using agar diffusion method. Eight different microorganisms were used in this study, that are Escherichia coli (Gram negative bacteria), Staphylococcus aureus and Bacillus cereus (Gram positive bacteria), Candida albicans and C. humicola (yeast), and Trichophyton mentagrophytes, T. rubrum and Microsporum canis (fungi). The broad spectrum of inhibition was exhibited by the essential oil of P. obtusa. The extract inhibited all tested microorganisms except for E. coli. The largest inhibition zone was shown by the P. obtusa essential oil against C. humicola. Komponen kimia minyak pati daripada bunga bagi tiga spesies Plumeria yang banyak terdapat di Malaysia, iaitu P. rubra L. (varieti bunga merah), P. acutifolia Poir. (varieti bunga kuning) dan P. obtusa L. (varieti bunga putih) telah dianalisis menggunakan GC/MS dan 27 komponen telah dikenal pasti. Tujuh komponen telah disisihkan dan dikenal pasti daripada P. rubra, 14 komponen daripada P. obtusa dan 19 komponen daripada P. acutifolia. Kandungan utama minyak pati bagi ketiga-tiga spesies ialah asid 2-hidroksibenzoik fenilmetil ester. Ketiga-tiga spesies juga berkongsi dua hidrokarbon alkana, iaitu nanodekana and heneikosana. Kesan antimikrob bagi minyak pati tersebut (pada 2 ?l bagi setiap disk) telah ditentukan menggunakan kaedah penyerapan agar. Lapan mikroorganisma telah digunakan untuk kajian ini, iaitu Escherichia coli (bakteria Gram negatif), Staphylococcus aureus dan Bacillus cereus (bakteria Gram positif), Candida albicans dan C. humicola (yis), dan Trichophyton mentagrophytes, T. rubrum dan Microsporum canis (kulat). Spektrum perencatan yang terluas ditunjukkan oleh minyak pati P. obtusa. Ekstrak tersebut merencat semua mikroorganisma yang diuji kecuali E. coli. Zon perencatan terbesar pula ditunjukkan oleh minyak pati P. obtusa terhadap C. humicola.